SEARCH for GAMMA-RAY EMISSION from the COMA CLUSTER with SIX YEARS of FERMI-LAT DATA - M. Ackermann (2018)
© 2016. The American Astronomical Society. All rights reserved.. We present results from γ-ray observations of the Coma cluster incorporating six years of Fermi-LAT data and the newly released "Pass 8" event-level analysis. Our analysis of the region reveals low-significance residual structures within the virial radius of the cluster that are too faint for a detailed investigation with the current data. Using a likelihood approach that is free of assumptions on the spectral shape we derive upper limits on the γ-ray flux that is expected from energetic particle interactions in the cluster. We also consider a benchmark spatial and spectral template motivated by models in which the observed radio halo is mostly emission by secondary electrons. In this case, the median expected and observed upper limits for the flux above 100 are 1.7 times;10-9 ph cm-2 s-1 and 5.2 times;10-9 ph cm-2 s-1 respectively (the latter corresponds to residual emission at the level of 1.8σ). These bounds are comparable to or higher than predicted levels of hadronic gamma-ray emission in cosmic-ray (CR) models with or without reacceleration of secondary electrons, although direct comparisons are sensitive to assumptions regarding the origin and propagation mode of CRs and magnetic field properties. The minimal expected γ-ray flux from radio and star-forming galaxies within the Coma cluster is roughly an order of magnitude below the median sensitivity of our analysis.